Capital Market Reaction: Stock Return, Abnormal Return, and Stock Trading Volume Before and After Stock Split (Case Study on Companies Listed on the Indonesia Stock Exchange) - Flowren, Elsha (STIE Amkop Makassar, 2025)
Stock split is one of the policies carried out by the company with the aim of rearranging the share price to make it more liquid so that it can be at an optimal trading level. This study aims to analyze the differences in stock returns, abnormal returns, and stock trading volume before and after stock splits. The population of this study were 38 companies with a sample of 32 companies on the Indonesia Stock Exchange for the period 2020-2023. Using secondary data with event study analysis techniques for a period of five days before and five days after the stock split event. This research uses a normality test and hypothesis testing in the form of a paired sample t test to determine the average difference between two related sample groups.